2016
DOI: 10.1016/j.sxmr.2015.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Gender Dysphoria and Autism Spectrum Disorder: A Systematic Review of the Literature

Abstract: Introduction. There is a growing clinical recognition that a significant proportion of patients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
114
4
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(126 citation statements)
references
References 59 publications
5
114
4
3
Order By: Relevance
“…4345 The most widely cited evidence supporting this hypothesis comes from a study of 204 children and/or adolescents referred to the Gender Identity Clinic in Amsterdam. 46 The presence of an autism spectrum disorder was established via a standardized diagnostic interview, 47 yielding a prevalence of 10% among transfeminine patients and 4% among transmasculine patients, which was reported by the authors to be higher than the 1% estimate reported in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…4345 The most widely cited evidence supporting this hypothesis comes from a study of 204 children and/or adolescents referred to the Gender Identity Clinic in Amsterdam. 46 The presence of an autism spectrum disorder was established via a standardized diagnostic interview, 47 yielding a prevalence of 10% among transfeminine patients and 4% among transmasculine patients, which was reported by the authors to be higher than the 1% estimate reported in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with GD may undergo hormonal and surgical interventions in order to align their experienced and assigned genders, and/or may socially transition by changing their pronouns and appearance to that of their identified gender. Higher rates of GD have been found amongst autistic individuals than in the general population [86], and the rate of ASD traits and ASD within individuals with GD is also significantly higher than average [87]. This again suggests there may be shared factors between both conditions, and suggests populations in which to examine for ASD.…”
Section: Gender Dysphoriamentioning
confidence: 96%
“…Transgender issues in the context of ASD have shown new developments that were not captured when the search for the current study was conducted, including two case studies of high-functioning individuals diagnosed with ASD and gender dysphoria (Jacobs, Rachlin, Erickson-Schroth, & Janssen, 2014), a report documenting autistic features in young people with gender dysphoria (Skagerberg, Di Ceglie, & Carmichael, 2015), two reviews about co-occurring gender dysphoria and ASD (up to 20%) (Glidden, Bouman, Jones, & Arcelus, 2016;Van Der Miesen, Hurley, & De Vries, 2016), and initial clinical guidelines for co-occurring ASD and gender dysphoria or incongruence in adolescents (Strang et al, 2016).…”
Section: Intellectual Disability/autism Spectrum Disordersmentioning
confidence: 99%